Yes because 3×2= 6 , 3×5= 15, 15 + 6 = 21
Answer: 3.5
Step-by-step explanation: divide 49 by 14
Hey there :)
- tan²x + sec²x = 1 or 1 + tan²x = sec²x
sin²x + cos²x = 1
Divide the whole by cos²x
![\frac{sin^2x}{cos^2x} + \frac{cos^2x}{cos^2x} = \frac{1}{cos^2x}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsin%5E2x%7D%7Bcos%5E2x%7D%20%2B%20%5Cfrac%7Bcos%5E2x%7D%7Bcos%5E2x%7D%20%3D%20%5Cfrac%7B1%7D%7Bcos%5E2x%7D%20)
![\frac{sinx}{cosx} = tanx](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsinx%7D%7Bcosx%7D%20%3D%20tanx)
so
![\frac{sin^2x}{cos^2x} = tan^2x](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsin%5E2x%7D%7Bcos%5E2x%7D%20%3D%20tan%5E2x)
and
![\frac{1}{cosx} = secx](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bcosx%7D%20%3D%20secx%20)
so
![\frac{1}{cos^2x} = sec^2x](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bcos%5E2x%7D%20%3D%20sec%5E2x)
Therefore,
tan²x + 1 = sec²x
Take tan²x to the other side {You will have the same answer}
1 = - tan²x = sec²x or sec²x - tanx = 1
Answer:
Solution given:
b=9 base side of isosceles triangle
a=![\sqrt{9²+9²}=9\sqrt{2}](https://tex.z-dn.net/?f=%20%5Csqrt%7B9%C2%B2%2B9%C2%B2%7D%3D9%5Csqrt%7B2%7D)
Answer:
A lot of work, but CD=$15, Premium=$35, and Deluxe=$85